The Medium is Viral: Reinterpreting McLuhan's Theory in Digital Da'wah Practice - Alhimni Fahma (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2026)
This study examines the practice of digital da‘wah through the lens of classical communication theory, particularly the medium is the message (Marshall McLuhan) and simulacra (Jean Baudrillard). The phenomenon of da‘wah on social media platforms such as TikTok and Instagram reveals that virality is no longer merely a channel of distribution but has become the dominant medium that shapes message structures, aesthetics, and digital religious practices. A qualitative approach employing content analysis and interviews was used to explore how repetitive, short-form da‘wah content creates a religious hyperreality detached from transcendental references. The findings indicate that: (1) the digital da‘wah landscape has shifted from educative-transformative communication toward performative expression governed by algorithmic logic; (2) religious symbols are massively reproduced in uniform and emotional formats, generating sign repetition; and (3) virality itself has emerged as the medium reshaping da‘wah into a phenomenon of aesthetic religiosity, where audience reception is formed as instant collective emotion based on visual impressions and digital popularity. This study underscores the need for a critical reading of digital da‘wah content to avoid entrapment in superficial and illusory forms of religious consumption.